In-vivo Anti-Angiogenic Activity of 2-Methoxyestradiol in Sarcoma 180 Tumour Cell Line - Srabantika Mallick; Samarendra Nath Banerjee (Medicine and Medical Research: New Perspectives Vol. 4, 2024)
Cancer is a complex genetic disease. Since the last few decades, the incidence of cancer has increased in different parts of the world, and now the situation is very alarming. Cancer or tumour cells are disorganized, mitotically uncontrolled, and autonomous race of cell populations, which consistently violate the basic rules of cell division. Most primary tumours arising in humans are benign. Benign tumours are harmless in a sheath of fibrous tissue, with a few exceptions. It cannot spread through other tissues. Some tumour cells may cause clinical problems and harm that migrate to distant body sites, forming secondary tumours. This process is known as metastasis, which is dependent on angiogenesis. The process of angiogenesis, the formation of new blood vessels from preexisting ones, is a fascinating and critical aspect of tumour growth and metastasis. This intricate process, which involves a complex interplay of factors, is a crucial area of research in the fight against cancer. Most cancer treatments aim to target metastasis. Presently, surgery, radiation therapy, chemotherapy, combination chemotherapy, immunotherapy, hormone replacement therapy and anti-angiogenic therapy are standard methods of cancer treatment. Low-dose chemotherapy combined with an anti-angiogenic drug therapy presents a promising approach to cancer treatment. The combination treatment of low-dose Cyclophosphamide – a cost-effective chemotherapeutic drug, with 2- Methoxyestradiol – a novel anti-angiogenic component, significantly enhances therapeutic efficacy. This is evidenced by the increased frequency of non-viable cell population, apoptosis, and survivability rate of the tumour-bearing host. 2-Methoxyestradiol (2-ME), an endogenous oestrogen metabolite, has been identified as a significant player in cancer therapy. Its ability to induce antiproliferative and apoptotic activities against proliferating cells and growing tumours, coupled with its dual nature of stimulating and inhibiting tumour angiogenesis and growth, underscores its importance in the field. Therefore, the biology of cancer cells is different than normal cells, and cancer biology research involves the realization of the biology of cancer to develop more avenues to diagnose, prevent, and treat cancer. This study provides an overview of some aspects of cancer biology.